If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6x+39=-4x+22
We move all terms to the left:
-6x+39-(-4x+22)=0
We get rid of parentheses
-6x+4x-22+39=0
We add all the numbers together, and all the variables
-2x+17=0
We move all terms containing x to the left, all other terms to the right
-2x=-17
x=-17/-2
x=8+1/2
| 7-5+3x-1=7x+0 | | 2-6s=62 | | -.05y+y=8.5 | | 7-5+3x-1=5x+9 | | b/5-4=4 | | 15x-51=10x-31 | | 7-5+3x-1=8x+2 | | 3(j-92)=9 | | -9x-10=-5x-6 | | 6t-21=15 | | 1/3-(x-7)/6=x^2-x/6 | | -19x+48=-12x+27 | | j/5-1=5 | | 29=-7v+3(v+3) | | 7=3s-11 | | x^2-12x-55=0 | | -18x-18=-11x-11 | | 2+3d=14 | | 36=3(y-6)+6y | | -12x-59=-6x-35 | | 7x+23=-4x+14 | | 9(u+7)-2u=20 | | 7-5+3x-1=4x+0 | | -15x+57=-10x+37 | | -28=-6w+2(w-4) | | -4x+23=-2x+17 | | x2–2x=146 | | -9x-31=-6x-19 | | 6b-4b=18-6 | | z^2+50=0 | | 14x+12=9x+7 | | |x-5|+6=10 |